FT-IR microscopic studies on coupling agents: treated natural fibres - Singh, B.; Gupta, M.; Verma, A.; Tyagi, O.S.
Natural fibres (sisal)were treated with various coupling agents such as organosilane, zirconate, titanate and N-substituted methacrylamide. The nature of the adsorbed chemical species on the fibre surfaces was analysed by Fourier transform infrared microscopy (FT-IR). The presence of precipitated oligomers on the surface was confirmed by the appearance of hydrogen-bonded carbonyl group and unsaturation bands. The results showed an irregular physisorption/chemisorption of coupling agents, their penetration beyond the surface, and a decrease in the hydrophilicity of fibres. SEM and dynamic contact angle studies on the fibres supported these findings. FT-IR microscopy in its reflectance mode was more effective in ascertaining the chemical nature and structure of adsorbed layers onto sisal fibre surfaces compared with DRIFT and transmission spectroscopy. The difference in the properties of untreated and chemically treated fibres has also been verified in the polymer composites.
Keywords: SISAL FIBRE; COUPLING AGENT; SURFACE TREATMENT; IR MICROSCOPY